2014
DOI: 10.1177/1753495x13518319
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate for eclampsia prevention: Quality of care evaluation in a tertiary centre in Québec, Canada

Abstract: Background: The current Canadian guidelines endorse the use of MgSO 4 for treatment of eclampsia and for prophylaxis in severe preeclampsia.Our study aimed to audit our institution's compliance regarding these guidelines. Methods:We conducted a retrospective study to evaluate MgSO 4 use in: all our cases of eclampsia since 2002, 50 cases of severe preeclampsia, and 50 cases of non-severe preeclampsia.Results: Sixty-five cases of preeclampsia were analyzed after initial chart review. A high rate of preeclampsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…The adherence rate for time of MgSO4 use was 20.79%. Similar findings have been previously reported [12,13]. However, Shields et al showed that high levels of compliance can be achieved in a relatively short period of time [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The adherence rate for time of MgSO4 use was 20.79%. Similar findings have been previously reported [12,13]. However, Shields et al showed that high levels of compliance can be achieved in a relatively short period of time [16].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies evaluating drug therapy guideline adherence for HDPs have mainly focused on the time of drug use [11][12][13], and guideline adherence regarding the route of administration and drug dosage is unknown, especially in China. The associations between drug therapy guideline adherence for HDPs and recommendation evidence are also unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Underutilization of magnesium sulphate among women with ‘severe’ pre-eclampsia is consistent with other studies, whether they be single-centre studies in Canada [ 16 ] or multicentre international studies [ 12 ]. Variation in opinion about what constitutes ‘severe’ pre-eclampsia is reflected in between-protocol variation in 22 Canadian tertiary hospitals and within-hospital differences in protocol and practice [ 17 ].…”
Section: Discussionsupporting
confidence: 89%